Retirement and subjective well-being - Eric Bonsang; Tobias J. Klein (Institute for the Study of Labor (IZA), 2011)
We provide an explanation for the common finding that the effect of retirement on life satisfaction is negligible. For this we use subjective well-being measures for life and domains of life satisfaction that are available in the German Socio-Economic Panel (GSOEP) and show that the effect of voluntary retirement on satisfaction with current household income is negative, while the effect on satisfaction with leisure is positive. At the same time, the effect on health satisfaction is positive but small. Following the life domain approach we then argue that these effects offset each other for an average individual and that therefore the overall effect is negligible. Furthermore, we show that it is important to distinguish between voluntary and involuntary retirement. The effect of involuntary retirement is negative because the adverse effect on satisfaction with household income is bigger, the favorable effect on satisfaction with leisure is smaller, and the effect on satisfaction with health is not significantly different from zero. These results turn out to be robust to using different identification strategies such as fixed effects and first differences estimation, as well as instrumental variables estimation using eligibility ages and plant closures as instruments for voluntary and involuntary retirement.
urn:nbn:de:101:1-201104133386
Keywords: J26; J14; 330; retirement; subjective well-being; satisfaction measurement; Altersgrenze; Flexible Altersgrenze; Zufriedenheit; Schätzung; Deutschland